Functions of legal guarantees of the rights and freedoms of human and citizen - Rustembekova, D.K. (Bulletin of the Karaganda University “Law Series”, 2018)
In accordance with the functions of legal guarantees, in the legal literature, it is rather common to divide the latter into guarantees: implementation; protection; protection of individual rights and freedoms. In addition, the fundamental rights of freedom of man and citizen are fixed at the constitutional level as directly acting, which gives them the highest legal force with regard to law-making, law-enforcement, law enforcement activities of all state bodies and officials. Realization of rights and freedoms is impossible without their protection, there is no such right that would not need protection. Under the protection of rights and freedoms, one should understand the state of lawful realization of rights and freedoms under the control of state bodies, public organizations, officials, but without their intervention. Measures for the protection of rights and freedoms operate in conditions where the exercise of rights and freedoms is difficult, but the rights and freedoms are not yet violated. One of the defining criteria for the difference between «protection» and «protection» is the form of activity of the relevant actors involved in ensuring rights and freedoms. In many respects, the guarantees of the realization of rights and freedoms are provided by the possibilities of guarantees of protection and protection. Thus, we can draw the following conclusion that the existence of a law-based state is in itself a legal guarantee in a broad sense, since it is in such a state that «a genuine triumph of law and law, the inviolability of the rights and freedoms of citizens» is ensured. It is the rule of law that has as its goal the most complete guarantee of the rights and freedoms of man and citizen.